Faktor Penentu Adopsi Pemasaran Media Sosial di Kalangan Petani Milenial Kabupaten Banyumas: Pendekatan Technology Acceptance Model - Yordan Hermawan Apidana; Pradita, Nanang (Journal of Agribusiness Science and Rural Development, 2024)
Marketing through social media is emerging as an effective tool for farmers to reach and interact with a wider range of customers, but with the low level of social media adoption among millennial farmers, systematic efforts are needed to identify barriers and opportunities that can be optimized through a more comprehensive approach. This study aims to explore the factors that influence the adoption of social media marketing among millennial farmers in Banyumas Regency using the Technology Acceptance Model (TAM) approach. The research method used was a quantitative survey involving 238 millennial farmers as respondents. The variables measured include perceived entertainment, perceived credibility, reference group influence, perceived ease of use, and perceived benefits. The results showed that perceived entertainment, perceived credibility, reference group influence and perceived usefulness had a positive and significant influence on farmers' attitudes towards social media marketing, while perceived ease of use was found to be insignificant. These findings indicate that aspects of entertainment, credibility, perceived benefits, as well as reference group support are crucial in encouraging millennial farmers to adopt social media marketing. The conclusion of this study emphasizes the importance of training programs that focus on improving digital skills and effective social media marketing strategies to support the sustainability and welfare of millennial farmers in Banyumas Regency.